2018
DOI: 10.1007/s40256-017-0258-8
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Reperfusion Injury with Intracoronary N-Acetylcysteine in Patients with STEMI Undergoing Primary Percutaneous Coronary Intervention in a Cardiac Tertiary Center

Abstract: In this study, NAC improved myocardial reperfusion markers and coronary blood flow, as revealed by differences in peak hs-TnT and TIMI flow grade 3 levels, respectively. Further studies with large samples are warranted to elucidate the role of NAC in this population. ClinicalTrials.gov identifier: NCT01741207, and the Iranian Registry of Clinical Trials (IRCT; http://irct.ir ) registration number: IRCT201301048698N8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…NAC was able to reduce the levels of ROS and increase cell survival during ischemia-reperfusion, suggesting that ROS reduction is involved in the protection against ischemia-reperfusion afforded by shifting metabolism towards increased glycolysis. Although the reduction of ROS has been associated with protection against ischemia-reperfusion injury [20] and the administration of high dose NAC to STEMI patients was able to reduce troponin levels and improve coronary blood flow [38], our results are the first evidence linking ROS with the protective mechanism of metabolic shift.…”
Section: Discussionmentioning
confidence: 55%
“…NAC was able to reduce the levels of ROS and increase cell survival during ischemia-reperfusion, suggesting that ROS reduction is involved in the protection against ischemia-reperfusion afforded by shifting metabolism towards increased glycolysis. Although the reduction of ROS has been associated with protection against ischemia-reperfusion injury [20] and the administration of high dose NAC to STEMI patients was able to reduce troponin levels and improve coronary blood flow [38], our results are the first evidence linking ROS with the protective mechanism of metabolic shift.…”
Section: Discussionmentioning
confidence: 55%
“…Nozari et al performed a randomized, double-blind, placebo-controlled trial, wherein they administered NAC before and during reperfusion. This resulted in a significant decrease in hs-TNT levels in patients supplemented with NAC versus the placebo, along with a higher percentage of patients with TIMI 3 flow in those who received the drug [ 105 ]. However, this study did not measure infarct size or other oxidative stress biomarkers.…”
Section: Cardioprotective Effects Exerted By Other Antioxidantsmentioning
confidence: 99%
“…24) NAC is an effective antioxidant, which can directly scavenge hydroxyl free radicals, 25) which can reduce the oxidative damage of target tissues and allow for sufficient oxygen consumption. 26) Nozari, et al 10) found that injecting a high dose of NAC before PCI significantly reduced the hs-TnT level and improved coronary perfusion caused by thrombolysis in myocardial infarction (TIMI) flow after PCI. Pasupathy,et al 11) demonstrated that the infarct size decreased in patients with acute STEMI after PCI when a large dose of NAC was injected intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…Randomization was mentioned in all studies. However, 8 studies [8][9][10][11][12][13]15,16) expounded the generation of random sequences. Only one study 8) described allocation concealment.…”
Section: Basic Information Of the Included Literaturementioning
confidence: 99%
See 1 more Smart Citation